Inovasi Produk Akad Qardhal Hasan (Pinjaman Modal Usaha) - Husna Wahida; Fani Indriani; Riandi Fauzi; Husni Kamal (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research uses a qualitative method with a descriptive approach through field studies to explore in depth the implementation of product innovation in Qardh Hasan contracts in the form of business capital loans at Islamic financial institutions. The aim of this study is to understand how Qardh Hasan products function not only as interest-free financing solutions but also as tools for empowering micro and small enterprises. Data was collected through in-depth interviews with institution managers, field officers, and beneficiary customers, as well as through documentation and direct observation of the loan distribution process. The findings reveal that innovations in managing Qardh Hasan products—such as community-based approaches, business mentoring, and entrepreneurship training—can enhance the effectiveness of fund utilization and strengthen the sustainability of micro-businesses. The use of data triangulation confirms that the success of this product largely depends on transparency, social proximity, and the institution’s commitment to upholding Sharia values. This study provides a valuable contribution to the development of socially based Sharia financing models for fostering economic self-reliance within communities.